One-way shear and punching strength of reinforced concrete slabs without transverse reinforcement under concentrated loads - Sousa, Alex Micael Dantas de (2022)
Most studies that address the shear behavior of reinforced concrete slabs without transverse reinforcement deal with slab strips loaded over the entire width or the punching capacity of flat slabs or slab-column connections. Therefore, these studies focus on slabs subjected to specific shear failure mechanisms. However, in the case of concentrated or partially distributed loads in small areas close to the support of one-way slabs, a frequent situation in bridge deck slabs, both one-way shear and punching shear failure mechanisms can occur. This study developed recommendations to assess the shear and punching shear strength of such slabs using different approaches. In this study, some recommendations were developed that are based on the use of only analytical expressions, others combining analytical expressions with results from linear elastic finite element analyses, others using non-linear finite element analyses, and, finally, using experimental investigations. Since both shear failure mechanisms can be critical for such slabs, the research was addressed in parts. Firstly, the one-way shear behavior of wide beams and slabs loaded over the entire width was addressed. After, different approaches used to define the effective shear width were investigated, combined with code expressions and also mechanical-based models of one-way shear strength. In the next step, the research addressed the combination of analytical expressions with linear elastic finite element analyses to predict the shear and punching shear strength of one-way slabs. In the context of punching, the research addressed the behavior and punching resistance of slabs designed with the rational use of ultra- high-performance fiber-reinforced concrete. Non-linear finite element analyses were also proposed to assess the failure mechanism and ultimate capacity of different kinds of slabs. In the end, an experimental program was performed to investigate the failure mechanism of one-way slabs under concentrated loads after local reinforcement yielding. In summary, this study addresses different approaches to design reinforced concrete slabs under concentrated loads based on a comprehensive review and analyses of different tests from literature and also performed herein. Besides, the experimental program confirmed important aspects of the shear redistribution at failure that resulted in a clear activation of different failure mechanisms.